Research on the Brand Construction Strategy of Xingcheng Duobao Fish Under the Background of Rural Revitalization - SUN Zhaowei; DONG Zhijing (Haiyang Kaifa yu guanli)
Branding is the only way to promote agricultural modernization. Xingcheng Duobao Fish is a brand case of creating regional characteristic agricultural products in Huludao City, Liaoning Province. Its successful experience has important reference significance for the development of regional characteristic agricultural product brands in Huludao. The paper deeply grasps the success factors of Xingcheng Duobao Fish brand building through on-site visits and literature review research, starting from natural conditions, brand positioning, business models, development strategies, and other methods. Based on this, it proposes suggestions for the development of regional characteristic agricultural product brands in Liaoning Province, aiming to deeply develop fishery resources and achieve the goal of promoting regional development through characteristic fisheries, also assist in the high-quality development of Huludao Port in Liaoning Province.